Perceived Ease of Use dan E-Service Quality terhadap Loyalitas Pengguna Aplikasi Kopi Kenangan di Kota Medan - Sitorus, Sabrina; Simanjorang, Feronica (Universitas 17 Agustus 1945 Surabaya, 2025)
Technological developments and digitalisation are driving changes in the business world, where both production and consumption activities are increasingly digitally driven and in demand. Kopi Kenangan, as one of Indonesia's F&B businesses, leverages technology and offers a mobile application to its customers to enhance customer satisfaction and loyalty. This study aims to analyse the influence of perceived ease of use and e-service quality on user loyalty for the Kopi Kenangan application in Medan City. This research uses a quantitative method with an associative approach. Researchers distributed questionnaires to 97 respondents obtained through purposive sampling techniques. The data obtained were analyzed using PLS-based Structural Equation Modeling (SEM) techniques. The research results indicate that perceived ease of use has a positive and significant influence on user loyalty, with a t-statistic value of 9.669 and significance < 0.05. The e-service quality variable has a positive and significant influence on user loyalty, with a t-statistic value of 2.196 and significance < 0.05. Simultaneously, perceived ease of use and e-service quality significantly influence user loyalty, accounting for 48.92%.